QTc prolongation and antipsychotic medications in psychiatric patients – a review - Zainuddin, Zahirah; Zaini, Syahrir (Malaysian Psychiatric Association, 2017)
Antipsychotic medications are the cornerstones of the acute and long-term treatment of schizophrenia. Despite their benefits in minimizing the schizophrenia symptoms, they have been associated with the risk of inducing QTc prolongation, which may lead to a serious life-threatening arrhythmia and cause sudden death. Objective: To review the QTc prolongation caused by antipsychotic medications used among psychiatric patients. Methods: Literature search was conducted using databases such as Scopus, Science Direct, Pubmed, and Springer link. The keywords used for the search were “QTc prolongation”, “antipsychotic medications” and “schizophrenia”. The inclusion criteria are articles from 2001 to 2014, articles written in English and articles related to the effects of antipsychotics in causing sudden cardiac death. The inclusion criteria are the articles written in other languages and the article about other adverse effect of antipsychotics. Results: Twenty-seven articles were found to be relevant to this study and twenty of them which discusses about antipsychotic-induced QT interval prolongation have been included in the table of evidence. Conclusion: Antipsychotics regardless of the generations have the potential of causing QT interval prolongation. The risk-to-benefit ratio that accounts for the danger of sudden cardiac death should be evaluated before prescribing an antipsychotic medicine and each individual patient should be assessed on the potential contributing factors to the prolongation of QTc.